CONFLICT TRANSFORMATION AND WELFARE OF INDIGENOUS PAPUAN COMMUNITIES IN THE NEW AUTONOMOUS REGION - Rais, Lukman; Nikmatul Ula, Siti Nurul; Berae, Agustinus; Ramli, Umar; Mardliyah, Uswatul (Universitas Padjadjaran, 2024)
The objectives of this study are to (1) investigate the relationship between conflict transformation and local community life and local wisdom, (2) the impact of conflict transformation on the common good, (3) the impact of local autonomy on the common good of indigenous Papuans. This study uses a mixed-methods approach with a multistage random sampling technique. Data collection was done through observations, in-depth interviews, questionnaires, and document reviews, which were analyzed using a parallel convergent mixed-methods design. This study shows that conflict transformation starts with a fair and equitable policy that prioritizes the advancement of indigenous Papuans while protecting local wisdom. In the subtests, conflict transformation and the formation of a new autonomous region have a positive and significant impact on the common good with t-table values of 3.983 (t-table = 1.960) and 2.475 (t-table = 1.960) The significance level is less than 0.05. The simultaneous test showed that conflict transformation and the formation of new autonomous regions had a positive and significant impact on the well-being of indigenous Papuans, with a calculated f-value of 76.821 (f-table = 3.04). This study provides new evidence that conflict transformation and the formation of new autonomous regions have increased the well-being of indigenous Papuans, a new finding not found in previous studies.Penelitian ini bertujuan untuk menganalisis (1) transformasi konflik dan hubungannya dengan kehidupan dan kearifan lokal masyarakat, (2) pengaruh transformasi konflik terhadap kesejahteraan masyarakat, (3) l pengaruh otonomi daerah terhadap kesejahteraan masyarakat asli papua. Penelitian ini menggunakan pendekatan metode campuran dengan teknik multi stage random sampling. Pengumpulan data dilakukan melalui observasi, wawancara mendalam, kuesioner, dan telaah dokumen yang dianalisis menggunakan desain metode campuran paralel konvergen. Temuan penelitian menunjukkan bahwa transformasi konflik diawali dengan kebijakan yang adil dan merata yang mengutamakan kemajuan masyarakat asli Papua dengan tetap menjaga kearifan lokal. Pada uji parsial transformasi konflik dan pemberntukan daerah otonomi baru berpengaruh positif dan signifikan terhadap kesejahteraan masyarakat dengan nilai t tabel masing-masing sebesar 3,983 (t tabel = 1.960) dan 2,475 (t tabel = 1.960) serta tingkat signifikansi di bawah 0,05. Pada uji simultan Transformasi konflik dan pembentukan daerah otonomi baru berpengaruh positif dan signifikan terhadap kesejahteraan masyarakat asli papua dengan nilai fhitung sebesar 76,821 (f tabel = 3.04). Studi ini mengungkap bukti baru bahwa transformasi konflik dan pembentukan daerah otonomi baru telah meningkatkan kesejahteraan masyarakat asli Papua, sebuah temuan baru yang tidak ditemukan dalam penelitian sebelumnya.